Pemberdayaan Ibu Hamil melalui Edukasi Kesehatan Reproduksi dan Gizi Seimbang di Wilayah Kerja PKM Bonehau - Anas, Hamdiah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Reproductive health and balanced nutrition are crucial for maintaining maternal health and fetal growth and development. Poor knowledge of nutritional patterns and reproductive health among pregnant women often leads to high rates of anemia, pregnancy complications, and stunting. The Bonehau Community Health Center (Puskesmas) is one of the areas with limited access to health information. Objective: This community service activity aims to empower pregnant women by increasing their knowledge and understanding of reproductive health and balanced nutrition. Methods: The activity was conducted in July 2025 in the Bonehau Community Health Center area, involving 40 pregnant women. The implementation method included a pre-test, reproductive health counseling, balanced nutrition education, interactive discussions, local nutrition menu simulations, and a post-test. Results: The average knowledge score of pregnant women increased from 58% (pre-test) to 87% (post-test). Most pregnant women expressed a commitment to regular antenatal checkups and adopting a balanced nutritional pattern. Conclusion: Education on reproductive health and balanced nutrition has proven effective in increasing the knowledge and awareness of pregnant women. This activity is expected to support the prevention of pregnancy complications and efforts to reduce stunting rates in the Bonehau Community Health Center's work area.